Tension type non-prestressed concrete pole and preparation method thereof

CN122878083APending Publication Date: 2026-10-09SHANDONG KAISHENG ELECTRIC POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611114400.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]通过增加普通增稠材料能够在一定程度上限制浆体迁移,但拌合物黏度过高时会增加连续布料和离心密实的阻力,并可能使纵向受力钢筋横肋附近的浆体填充不足

Benefits of technology

(1)本发明将粒化高炉矿渣粉和氢氧化钙在水相中预分散形成石灰调理矿渣浆,并在主搅拌机外预先制成能够独立计量的矿渣触变添加剂。相较于将各组分分别直接投入主体混凝土的方式,预先形成所述矿渣触变添加剂有利于提高各组分在浆态体系中的分散均匀性,减小离心成型过程中浆体和骨料的径向迁移,从而提高混凝土杆体截面的径向均匀性及纵向受力钢筋周围混凝土的握裹性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878083A_ABST
    Figure CN122878083A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of concrete, in particular to a tension type non-prestressed concrete pole and a preparation method thereof. The pole comprises a hollow annular concrete pole body containing a slag thixotropic additive and a steel reinforcement cage. Granulated blast furnace slag powder and calcium hydroxide are pre-dispersed in an aqueous phase, and a first part of attapulgite powder, an aqueous solution of aluminum sulfate octadecahydrate and a second part of attapulgite powder are sequentially added, and the obtained slag thixotropic additive is added after completion of wet mixing of the main body concrete. The longitudinal stress steel is arranged and centrifuged under temporary tension, and the external tension force is completely removed after the centrifugation is completed, before temperature curing and when the concrete is still in the plastic stage. The method is beneficial to reduce the radial difference of the pole section, maintain the steel reinforcement grip and make the finished longitudinal stress steel reinforcement non-prestressed steel reinforcement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete technology, and in particular to a tensioned non-prestressed concrete pole and its preparation method. Background Technology

[0002] Circular concrete poles typically achieve their hollow, thin-walled structure through a process of concrete placement, formwork assembly, and centrifugation. During centrifugation, the coarse aggregate, fine aggregate, water, and slurry in the mixture undergo varying degrees of radial migration, easily leading to differences in aggregate volume fraction, porosity, and moisture content among the outer, middle, and inner layers of the same cross-section. When granulated blast furnace slag powder is used to replace part of the ordinary Portland cement, the matching requirements between the early structural build-up rate and the slurry's resistance to radial migration become even more stringent.

[0003] Adding common thickeners can limit slurry migration to some extent, but excessively high viscosity of the mixture increases resistance to continuous spreading and centrifugal compaction, and may result in insufficient slurry filling near the transverse ribs of longitudinal reinforcing bars. While using accelerators alone can shorten the early structural build-up time, uneven addition locations and local concentrations can cause some slurry to lose fluidity prematurely, making it difficult to simultaneously achieve radial uniformity of the centrifugal cross-section and reinforcement bonding.

[0004] Regarding the positioning of the reinforcing cage, applying axial tension to the longitudinal reinforcing bars during molding helps maintain their straightness and concentricity. If the tension is maintained until the concrete reaches a high strength before unloading, the rebar shrinkage will transmit permanent prestress to the cage through the established bond, transforming the resulting product into a prestressed component. Conversely, unloading too early or too quickly after centrifugation may disturb the grout surrounding the reinforcing bars, which are still in the plastic stage. Therefore, it is necessary to coordinate the material state of the centrifuged concrete, the formation and feeding relationship of additives, and the timing of unloading during temporary tensioning. Summary of the Invention

[0005] In view of this, the purpose of this invention is to provide a tensioned non-prestressed concrete pole and its preparation method, so as to reduce the radial difference of the pole cross section, maintain the compactness and bonding of the concrete around the longitudinal reinforcing bars, and keep the longitudinal reinforcing bars in the finished product in a non-prestressed state during the centrifugal molding process of the annular concrete pole using granulated blast furnace slag powder.

[0006] To achieve the above objectives, the present invention provides a tensioned non-prestressed concrete pole, comprising a hollow annular concrete pole body and a reinforcing cage embedded in the concrete pole body. The reinforcing cage includes longitudinal reinforcing bars spaced apart along the circumference of the concrete pole body, spiral bars wound around the outside of the longitudinal reinforcing bars, and a support ring connecting the longitudinal reinforcing bars. The concrete pole body is composed of a concrete mix containing ordinary Portland cement, granulated blast furnace slag powder, medium sand, crushed stone, polycarboxylate superplasticizer, water, and slag thixotropic additive. The mixture is formed by molding, with the total mass of the ordinary silicate cement and all granulated blast furnace slag powder being 100 parts by mass, the ordinary silicate cement being 60-62 parts by mass, the granulated blast furnace slag powder being the balance, the two totaling 100 parts by mass, the medium sand being 165-168 parts by mass, the crushed stone being 252-255 parts by mass, the polycarboxylate-based high-efficiency water-reducing agent being 0.9-1.0 parts by mass, the total water being 32-34 parts by mass, and the wet dosage of the slag thixotropic additive being 13-19 parts by mass; The granulated blast furnace slag powder in the slag thixotropic additive is 100 parts by weight. The slag thixotropic additive contains 89.5-99.5 parts by weight of water, 4-7 parts by weight of calcium hydroxide, 6-10 parts by weight of aluminum sulfate octadecylhydrate, and 3-6 parts by weight of attapulgite powder. The water in the slag thixotropic additive is added liquid water during the preparation of the additive, and the total water is the sum of the added liquid water directly added to the main concrete and the water in the slag thixotropic additive. The slag thixotropic additive is a slurry additive that is independently prepared and metered in after the main wet mixing of the concrete mixture is completed. The slag thixotropic additive is formed by pre-dispersing granulated blast furnace slag powder and calcium hydroxide in an aqueous phase to form a lime-conditioned slag slurry, adding a first part of attapulgite powder to the lime-conditioned slag slurry, then adding an aqueous solution of aluminum sulfate octahydrate, and then adding a second part of attapulgite powder. The granulated blast furnace slag powder and water contained in the slag thixotropic additive are respectively included in the mass fraction of all granulated blast furnace slag powder and total water. The concrete bar is formed by placing and centrifuging the longitudinal reinforcing bars under temporary tension, and then completely removing the external tension of the longitudinal reinforcing bars after centrifugation and before heating and curing while the concrete is still in the plastic stage. The longitudinal reinforcing bars in the finished product are non-prestressed reinforcing bars.

[0007] Furthermore, with the total mass of the ordinary silicate cement and all granulated blast furnace slag powder as 100 parts by mass, the granulated blast furnace slag powder contained in the slag thixotropic additive accounts for 15.7% to 22.4% of the total granulated blast furnace slag powder; the ratio of the total water to the total mass of the ordinary silicate cement, all granulated blast furnace slag powder, calcium hydroxide, aluminum sulfate octadecylhydrate and attapulgite powder is 0.316 to 0.332.

[0008] Furthermore, the first portion of attapulgite powder accounts for 40% to 60% of the total mass of attapulgite powder, while the second portion of attapulgite powder is the remainder.

[0009] Furthermore, the longitudinal reinforcing bars are 12 HRB400 hot-rolled ribbed steel bars with a nominal diameter of 8mm, and the spiral bars and support rings are HPB300 plain round steel bars. The 12 longitudinal reinforcing bars are evenly distributed along the circumference of the concrete pole.

[0010] Furthermore, the present invention also provides a method for preparing a tensioned non-prestressed concrete pole, comprising the following steps: (1) Granulated blast furnace slag powder and calcium hydroxide are added to water for pre-dispersion to form lime-conditioned slag slurry; (2) Add the first part of attapulgite powder to the lime-conditioned slag slurry, stir, add aluminum sulfate octahydrate aqueous solution, continue stirring, and then add the second part of attapulgite powder to obtain an independent slag thixotropic additive. (3) Dry mix crushed stone, medium sand, ordinary silicate cement and granulated blast furnace slag powder directly into the main mixer, add water containing polycarboxylate superplasticizer for main wet mixing, and then add the slag thixotropic additive after the main wet mixing is completed and continue mixing to obtain centrifugal concrete. (4) Fabricate a steel cage containing longitudinal reinforcing bars, spiral bars and support rings, and temporarily tension the longitudinal reinforcing bars simultaneously, maintaining the temporary tension state to complete the placement, formwork closing and graded centrifugation of the centrifuged concrete; (5) After centrifugation, the external tension is completely removed to 0 while the concrete is still in the plastic stage and is not heated, and the external tension connection is removed; then low temperature curing, demolding and subsequent curing are carried out.

[0011] Furthermore, when forming the lime-conditioned slag slurry, the water temperature is controlled at 25°C. Granulated blast furnace slag powder and calcium hydroxide are added while stirring at 400 r / min, and then the stirring speed is increased to 500-700 r / min for 8-12 min. After adding the first part of attapulgite powder, the mixture is stirred for 2 min. Within 3-5 min, an aqueous solution of aluminum sulfate octadecylhydrate is added and stirring is continued for 5-8 min. After adding the second part of attapulgite powder, the mixture is stirred for 8-12 min. The resulting slag thixotropic additive can be stored in a sealed container and added to the centrifugal concrete within 40 min.

[0012] Furthermore, the crushed stone, medium sand, ordinary silicate cement, and granulated blast furnace slag powder directly added to the main mixer are dry-mixed for 30 seconds, then wet-mixed with water containing polycarboxylate-based high-efficiency water-reducing agent for 60 seconds, and then mixed for another 60-120 seconds after adding the slag thixotropic additive.

[0013] Furthermore, a temporary tension control stress of 60-100 MPa is applied to the longitudinal reinforcing steel bars, and the load is sequentially applied to 20%, 60%, and 100% of the corresponding total tension force. The first two stages are held for 30 seconds each, and the last stage is held for 60 seconds. The graded centrifugation includes running at 150 r / min for 2 minutes, at 400 r / min for 3 minutes, and at 800 r / min for 6 minutes, with a uniform speed increase of 30 seconds between adjacent stages.

[0014] Furthermore, after centrifugation stops, the mold remains closed and is not heated. When the penetration resistance of the mortar screened out of the same disc is 0.3 to 0.8 MPa, unloading begins. The external tension is first reduced to 50% of the total temporary tension force within 30 seconds, and then the external tension is uniformly reduced to 0 within 60 to 120 seconds. After unloading is completed, the external tension connection is removed, and no axial tension is applied to the longitudinal reinforcing steel in subsequent steps.

[0015] Furthermore, after completely removing the external tension, the mold was closed and left to stand for 10 minutes. The temperature was then increased to 40℃ at a rate of 10℃ / h and maintained for 6 hours. Heating was then stopped and the mold was allowed to cool down in the curing chamber. After the mold was closed for 12 hours and the compressive strength of the concrete specimens under the same conditions reached 15MPa, the specimens were demolded. After demolding, the specimens were cured at 20℃ and 95% relative humidity for 28 days.

[0016] The beneficial effects of this invention are: (1) In this invention, granulated blast furnace slag powder and calcium hydroxide are pre-dispersed in an aqueous phase to form lime-conditioned slag slurry, and a slag thixotropic additive that can be independently metered is pre-formed outside the main mixer. Compared with the method of directly adding each component to the main concrete, the pre-formation of the slag thixotropic additive is beneficial to improving the dispersion uniformity of each component in the slurry system, reducing the radial migration of slurry and aggregate during centrifugal molding, thereby improving the radial uniformity of the concrete bar cross section and the bonding performance of the concrete around the longitudinal reinforcing steel.

[0017] (2) In this invention, a first part of attapulgite powder is added to lime-conditioned slag slurry, followed by an aqueous solution of aluminum sulfate octadecylhydrate, and then a second part of attapulgite powder is added after stirring. By adding the slag thixotropic additive in stages, the static stability and structural recovery ability after shearing of the slag thixotropic additive can be improved, so that the slag thixotropic additive can still recover a suitable slurry structure after being subjected to mixing and conveying shearing, thereby improving the radial uniformity of centrifugal concrete and the bonding performance of steel bars.

[0018] (3) The present invention adds slag thixotropic additive by metering after the main concrete is wet-mixed, which can shorten the time when the slag thixotropic additive is subjected to high shear before being put into the mold, reduce the damage to the slurry structure of the slag thixotropic additive during the early wet mixing process of the main concrete, and help to exert the regulating effect of the slag thixotropic additive on the migration of centrifugal concrete materials, thereby reducing centrifugal radial stratification and improving the density and bonding performance of the concrete around the longitudinal reinforcing steel.

[0019] (4) The present invention implements temporary synchronous tensioning of longitudinal reinforcing bars during the fabrication and centrifugal molding process, which can maintain the straightness and circumferential distribution of longitudinal reinforcing bars, reduce the bending, displacement or asynchronous displacement of longitudinal reinforcing bars during fabrication, mold closing and centrifugal molding, thereby improving the positional stability of the reinforcing cage in the concrete rod and the consistency of the rod reinforcement.

[0020] (5) In this invention, after centrifugation and before curing, while the concrete is still in the plastic stage, the external tension of the longitudinal reinforcing bars is completely removed to 0, and no axial tension is applied in subsequent steps. Thus, the temporary tension of the longitudinal reinforcing bars is mainly used for positioning and stabilizing the bars during molding, which can reduce the permanent prestress transmitted to the concrete bar by the retraction of the reinforcing bars, so that the longitudinal reinforcing bars in the finished product remain in a non-prestressed reinforcing bar state, while taking into account the positional stability of the reinforcing bars during molding and the non-prestressed stress requirements of the finished product. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0022] Figure 1 This is a flowchart of the method for preparing tensioned non-prestressed concrete poles according to the present invention; Figure 2 The load-slip curves are for Example 1 and Comparative Examples 4, 5 and 9. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0024] The present invention will be further described below with reference to embodiments and accompanying drawings. In the embodiments, a 600mm equal-diameter ring-shaped pole segment is used as a process specimen with the same cross-sectional structure as an equal-diameter concrete pole. Its cross-sectional dimensions, reinforcement, unit volume mix ratio, temporary tension control stress, centrifugation regime, and unloading conditions are set according to the following steps. When manufacturing the equal-diameter concrete pole, a mold adapted to the target pole length is used, and the material is metered and laid according to the same unit volume mix ratio. The longitudinal reinforcing bars are set along the entire length of the pole, and temporary tension is applied simultaneously from both ends. The total tension is determined based on the total cross-sectional area of ​​the longitudinal reinforcing bars and the temporary tension control stress. The material formation sequence, the timing of additive addition, the centrifugation regime, the unloading during the plastic stage, and the curing steps are the same as in the embodiments described below.

[0025] The term "temporary tensioning" in this manual refers to the axial tensile force applied only during the fabric placement and centrifugal molding process to maintain the straightness, concentricity, and positional stability of the longitudinal reinforcing bars. The term "plastic stage" refers to the stage after centrifugation, before heat curing, and when the penetration resistance of the mortar sieved from the same tray is 0.3–0.8 MPa. The external tension force is completely removed during this stage, and no further axial tensile force is applied to the longitudinal reinforcing bars after unloading. When the 28-day converted residual average compressive stress is not greater than 0.2 MPa and the residual stress transfer rate is not greater than 5%, it indicates that the finished product has not formed a stress state based on pre-tensioning.

[0026] The "water" in the slag thixotropic additive referred to in this specification refers to the added liquid water used in the preparation of the slag thixotropic additive; the "total water" referred to in this specification refers to the sum of the added liquid water directly added to the main concrete and the added liquid water contained in the slag thixotropic additive. The water of crystallization contained in aluminum sulfate octahydrate is not included in the aforementioned "water" or "total water". Granulated blast furnace slag powder was purchased from Gulf Cement Company PSC, grade GGBS, with a specific surface area of ​​437 m². 2 / kg, 5.6% residue on 45μm sieve.

[0027] Attapulgite powder was purchased from BASF Corporation, grade ATTAGEL 50, with an average particle size of 9 μm and a typical bulk density of 400 kg / m³. 3 .

[0028] The ordinary Portland cement used is P·O42.5 ordinary Portland cement; the crushed stone is continuously graded crushed stone with a maximum nominal particle size of 20mm; the fineness modulus of the medium sand is 2.7; and the water-reducing agent is a powdered polycarboxylate-based high-efficiency water-reducing agent.

[0029] The reinforcing cage includes HRB400 longitudinal reinforcing bars, HPB300 spiral bars, and HPB300 support rings; the longitudinal reinforcing bars in the annular bar segment are hot-rolled ribbed steel bars with a nominal diameter of 8mm.

[0030] Test methods 1. Slag Thixotropic Additive State Test: Slurry samples were taken at 25℃ and filtered through a 0.45μm filter membrane. The absorbance of the filtrate was measured at 530nm after colorimetric analysis with aluminum reagent. Another filtrate was added to barium chloride and the turbidity absorbance at 420nm was measured. The solid phase was washed three times with deionized water and dried under reduced pressure at 40℃ for 24h. The total mass of granulated blast furnace slag powder, calcium hydroxide, aluminum sulfate octadecylhydrate, and attapulgite powder in the slurry was used as the corresponding original solid mass. The increase in solid mass after washing was expressed as the rate of change of solid mass relative to the original solid mass after washing and drying. The original slurry was placed in a 100mL graduated cylinder and allowed to stand for 30min. The height retention rate was expressed as the ratio of the deposition layer height to the initial slurry column height. The shear recovery rate was determined using rotational rheology: the sample was first subjected to a 1s... -1 Cut for 60 seconds, then cut again for 100 seconds. -1 Shear for 60 seconds, let stand for 300 seconds, and then shear again for 1 second. -1 The viscosity was calculated by applying a shearing test for 60 seconds and using the ratio of the apparent viscosity at the end of the recovery phase to the apparent viscosity at the end of the initial phase.

[0031] 2. Centrifugal Radial Stratification Index: The 28-day annular rod segment was divided into outer, middle, and inner layers along the wall thickness direction. After removing the reinforcing steel, equal-volume samples were obtained from each layer and dried at 105℃ to constant weight. The dry density of each layer was calculated. Centrifugal Radial Stratification Index I r Press I r The formula is calculated as (ρmax - ρmin) / ρavg, where ρmax, ρmin, and ρavg are the maximum, minimum, and average values ​​of the dry density in the three layers, respectively. Three independent ring-shaped segments are taken from each group, and the average value of the results for the three segments is listed in the table.

[0032] 3.0.1mm slip-bond stress: An arc-shaped specimen containing one longitudinal reinforcing bar was cut from a 28d annular segment. The actual anchorage length of the reinforcing bar was controlled to be 50mm. A single-end pull-out method was used, with a loading rate of 0.2mm / min, and the complete load-slip curve was recorded. 0.1mm slip-bond stress τ 0.1 Press τ 0.1 =P 0.1 / (πdl a ) calculate, where P 0.1 The load at which slippage reaches 0.1 mm, d is the nominal diameter of the steel bar, and l a This represents the actual anchorage length. Three independent specimens were taken from each group, and the average values ​​are listed in the table.

[0033] 4.1d compressive strength: Prepare matching concrete specimens with the same raw materials, formula, mixing sequence and curing regime, and test them according to the method specified in GB / T50081-2019.

[0034] 5. Initial setting time: The mortar was sieved from the mixture and tested according to the penetration resistance method of GB / T50080-2016. The time when the penetration resistance reached 3.5MPa was taken as the initial setting time.

[0035] 6.28d Length Change: Prepare matching test specimens with the same raw materials, formula and stirring sequence, and test according to the shrinkage test caliber specified in GB / T50082-2024. Negative values ​​indicate shrinkage, and positive values ​​indicate length increase.

[0036] 7. Residual Stress: For each group subjected to temporary tensioning, the shear release strain was measured on three longitudinal reinforcing bars selected in the middle of the 28d segment, and the shear release strain of the same reinforced segment in Comparative Example 9 was used as the shrinkage background for deduction; the values ​​of Comparative Example 9 in Table 4 are their converted values ​​without background deduction. The residual stress of the reinforcing bars was converted according to the elastic modulus of 200 GPa, and then the average residual compressive stress of the bar was converted according to the ratio of the total cross-sectional area of ​​the longitudinal reinforcing bars to the net cross-sectional area of ​​the concrete in the bar; the residual stress transfer rate is the ratio of the residual stress of the reinforcing bars to the temporary tensioning control stress.

[0037] 8. Radial position deviation of longitudinal reinforcing bars: Cross sections are cut at both ends and the middle of the 28d segment, and the actual radius from the center of each longitudinal reinforcing bar to the geometric center of the bar is measured. The maximum absolute difference between the actual radius and the average radius of the 12 longitudinal reinforcing bars is taken as the maximum radial position deviation of the longitudinal reinforcing bars. Example 1:

[0038] Step (1): Prepare lime-conditioned slag slurry. Add 550g of water to a 3L alkali-resistant stirring container, control the water temperature to 25℃, add 800g of granulated blast furnace slag powder and 45g of calcium hydroxide powder while stirring at 400r / min, raise the speed to 600r / min and maintain it for 10min.

[0039] Step (2) forms a thixotropic additive for slag. Dissolve 67g of aluminum sulfate octadechydrate in 202g of water; divide 36g of attapulgite powder into two equal portions. First, add 18g of attapulgite powder to the slurry obtained in step (1), stir at 500r / min for 2min, and then add all the aluminum sulfate octadechydrate aqueous solution within 4min. Continue stirring for 6min, then add the remaining 18g of attapulgite powder and continue stirring for 10min. Store the resulting slurry in a sealed container and use within 30min. Step (3): Prepare centrifugal concrete. Add 13.7 kg of crushed stone, 9 kg of medium sand, 3.3 kg of ordinary Portland cement and 1.7 kg of granulated blast furnace slag powder to a forced mixer and dry mix for 30 s; dissolve 50 g of powdered polycarboxylate superplasticizer in 1.4 kg of water and add it to the mixture and wet mix for 60 s. Weigh 850 g of the slag thixotropic additive obtained in step (2), add it after the main wet mixing is completed and continue mixing for 90 s; Step (4): Fabricate and temporarily tension the reinforcing cage. Use a uniform diameter annular segment mold with a length of 600mm, an outer diameter of 190mm, and a wall thickness of 50mm. Evenly arrange 12 HRB400 longitudinal reinforcing bars with a nominal diameter of 8mm along the circumference of the mold. The effective clamping length of the longitudinal reinforcing bars is 750mm. HPB300 spiral reinforcement and support rings are also provided. Temporary synchronous tensioning is implemented with a control stress of 80MPa. First, load to 20% of the total tension force of 48kN and hold for 30s, then load to 60% and hold for 30s, and finally load to 48kN and hold for 60s. The elastic elongation of the clamping section is 0.300mm.

[0040] Step (5), spreading and centrifugation. Maintain a total tension of 48 kN, continuously spread the concrete obtained in step (3) along the mold axis and close the mold; run at 150 r / min for 2 min to complete the spreading, run at 400 r / min for 3 min to complete the ring formation, and then run at 800 r / min for 6 min to complete the compaction. For adjacent stages, increase the speed uniformly for 30 s, and then brake and lock the mold.

[0041] Step (6), unloading during the plastic stage. After centrifugation stops, keep the mold and protective cover closed, and do not heat. When the penetration resistance of the mortar screened out of the same pan is 0.5MPa, start unloading. First, reduce the tension to 24kN within 30s, and then uniformly reduce it to 0 within 90s. After unloading, remove the external tensioning connection, and no further axial tension will be applied to the longitudinal reinforcing bars.

[0042] Step (7), low-temperature curing. After unloading, the mold is closed and left to stand for 10 minutes. The temperature is then increased to 40℃ at a rate of 10℃ / h and maintained for 6 hours. Heating is then stopped and the mold is allowed to cool with the curing chamber. The mold is removed after 12 hours of closure and when the compressive strength of the concrete specimen reaches 15MPa under the same conditions. If the strength does not reach 15MPa, curing continues with the mold closed. After demolding, the specimen is cured at 20℃ and 95% relative humidity for 28 days. Example 2:

[0043] Step (1): Prepare lime-conditioned slag slurry. Add 560g of water to a 3L alkali-resistant stirring container, control the water temperature to 25℃, add 800g of granulated blast furnace slag powder and 32g of calcium hydroxide powder while stirring at 400r / min, raise the speed to 500r / min and maintain it for 8min.

[0044] Step (2) forms a thixotropic additive for slag. Dissolve 48g of aluminum sulfate octadechydrate in 236g of water; divide 24g of attapulgite powder into two portions of 9.6g and 14.4g. First, add 9.6g of attapulgite powder to the slurry obtained in step (1), stir at 450r / min for 2min, and then add all the aluminum sulfate octadechydrate aqueous solution within 5min. Continue stirring for 5min, then add the remaining 14.4g of attapulgite powder and continue stirring for 8min. Store the resulting slurry in a sealed container and use within 40min. Step (3): Prepare centrifugal concrete. Add 13.7 kg of crushed stone, 9 kg of medium sand, 3.3 kg of ordinary Portland cement and 1.771 kg of granulated blast furnace slag powder to a forced mixer and dry mix for 30 s; dissolve 50 g of powdered polycarboxylate superplasticizer in 1.476 kg of water and add it to the mixture and wet mix for 60 s. Weigh 703 g of the slag thixotropic additive obtained in step (2) and add it after the main wet mixing is completed, and continue mixing for 60 s.

[0045] Step (4): Fabricate and temporarily tension the reinforcing cage. Using a uniform-diameter annular segment mold with a length of 600mm, an outer diameter of 190mm, and a wall thickness of 50mm, 12 HRB400 longitudinal reinforcing bars with a nominal diameter of 8mm are evenly arranged along the circumference of the mold. The effective clamping length of the longitudinal reinforcing bars is 750mm, and HPB300 spiral reinforcement and support rings are provided. Temporary synchronous tensioning is implemented with a control stress of 60MPa. First, the load is increased to 20% of the total tension force of 36kN and held for 30s, then increased to 60% and held for 30s, and finally increased to 36kN and held for 60s; the elastic elongation of the clamping section is 0.225mm.

[0046] Step (5), spreading and centrifugation. Maintain a total tension of 36kN, continuously spread the concrete obtained in step (3) along the mold axis and close the mold; run at 150r / min for 2min to complete the spreading, run at 400r / min for 3min to complete the ring formation, and then run at 800r / min for 6min to complete the compaction. For adjacent stages, increase the speed uniformly for 30s, and then brake and lock the mold.

[0047] Step (6), unloading during the plastic stage. After centrifugation stops, keep the mold and protective cover closed, and do not heat. When the penetration resistance of the mortar screened out of the same pan is 0.3MPa, start unloading. First, reduce the tension to 18kN within 30s, and then uniformly reduce it to 0 within 60s. After unloading is completed, remove the external tensioning connection, and no further axial tension will be applied to the longitudinal reinforcing bars.

[0048] Step (7), low-temperature curing. After unloading, the mold is closed and left to stand for 10 minutes. The temperature is then increased to 40℃ at a rate of 10℃ / h and maintained for 6 hours. Heating is then stopped and the mold is allowed to cool with the curing chamber. The mold is removed after 12 hours of closure and when the compressive strength of the concrete specimen reaches 15MPa under the same conditions. If the strength does not reach 15MPa, curing continues with the mold closed. After demolding, the specimen is cured at 20℃ and 95% relative humidity for 28 days. Example 3:

[0049] Step (1): Prepare lime-conditioned slag slurry. Add 540g of water to a 3L alkali-resistant stirring container, control the water temperature to 25℃, add 800g of granulated blast furnace slag powder and 56g of calcium hydroxide powder while stirring at 400r / min, raise the speed to 700r / min and maintain it for 12min.

[0050] Step (2) forms a thixotropic additive for slag. Dissolve 80g of aluminum sulfate octadechydrate in 176g of water; divide 48g of attapulgite powder into two portions of 28.8g and 19.2g. First, add 28.8g of attapulgite powder to the slurry obtained in step (1), stir at 600r / min for 2min, and then add all the aluminum sulfate octadechydrate aqueous solution within 3min. Continue stirring for 8min, then add the remaining 19.2g of attapulgite powder and continue stirring for 12min. Store the resulting slurry in a sealed container and use within 20min.

[0051] Step (3): Prepare centrifugal concrete. Add 13.7 kg of crushed stone, 9 kg of medium sand, 3.3 kg of ordinary Portland cement and 1.629 kg of granulated blast furnace slag powder to a forced mixer and dry mix for 30 s; dissolve 50 g of powdered polycarboxylate superplasticizer in 1.321 kg of water and add it to the mixture and wet mix for 60 s. Weigh 1 kg of the slag thixotropic additive obtained in step (2), add it after the main wet mixing is completed and continue mixing for 120 s.

[0052] Step (4): Fabricate and temporarily tension the reinforcing cage. Use a uniform diameter annular segment mold with a length of 600mm, an outer diameter of 190mm, and a wall thickness of 50mm. Evenly arrange 12 HRB400 longitudinal reinforcing bars with a nominal diameter of 8mm along the circumference of the mold. The effective clamping length of the longitudinal reinforcing bars is 750mm. HPB300 spiral reinforcement and support rings are also provided. Implement temporary synchronous tensioning with a control stress of 100MPa. First, load to 20% of the total tension force of 60kN and hold for 30s, then load to 60% and hold for 30s, and finally load to 60kN and hold for 60s. The elastic elongation of the clamping section is 0.375mm.

[0053] Step (5), spreading and centrifugation. Maintain a total tension of 60 kN, continuously spread the concrete obtained in step (3) along the mold axis and close the mold; run at 150 r / min for 2 min to complete the spreading, run at 400 r / min for 3 min to complete the ring formation, and then run at 800 r / min for 6 min to complete the compaction. For adjacent stages, increase the speed uniformly for 30 s, and then brake and lock the mold.

[0054] Step (6), unloading during the plastic stage. After centrifugation stops, keep the mold and protective cover closed, and do not heat. When the penetration resistance of the mortar screened from the same pan is 0.8 MPa, start unloading. First, reduce the tension to 30 kN within 30 seconds, and then uniformly reduce it to 0 within 120 seconds. After unloading, remove the external tensioning connection, and no further axial tension will be applied to the longitudinal reinforcing bars.

[0055] Step (7), low-temperature curing. After unloading, the mold is closed and left to stand for 10 minutes. The temperature is then increased to 40℃ at a rate of 10℃ / h and maintained for 6 hours. Heating is then stopped and the mold is allowed to cool with the curing chamber. The mold is removed after 12 hours of closure and when the compressive strength of the concrete specimen reaches 15MPa under the same conditions. If the strength does not reach 15MPa, curing continues with the mold closed. After demolding, the specimen is cured at 20℃ and 95% relative humidity for 28 days.

[0056] Comparative Example 1: Lime-conditioned slag slurry was prepared based on Example 1, but without aluminum sulfate octadechydrate and attapulgite powder. Each batch of concrete used 697.5g of lime-conditioned slag slurry, consisting of 400g granulated blast furnace slag powder, 22.5g calcium hydroxide, and 275g water. At the point of addition of additives after the main wet mixing was completed, an additional 101g of water and 51.5g granulated blast furnace slag powder were added, ensuring the total feed at that point remained 850g. The 33.5g aluminum sulfate octadechydrate and 18g attapulgite powder missing compared to Example 1 were made up with an equal mass of granulated blast furnace slag powder. The total concrete mass, total water, aggregate gradation, water-reducing agent, tensioning, centrifugation, unloading during the plastic stage, and curing regime were all the same as in Example 1.

[0057] Comparative Example 2: Based on Comparative Example 1, at the point when the additives were added after the main wet mixing was completed, 33.5g of the supplementary additives were replaced with 33.5g of aluminum sulfate octadechydrate by mass of granulated blast furnace slag powder. The aluminum sulfate octadechydrate was dissolved in 101g of water and directly added to the main mixer. Attapulgite powder was not added, and the missing 18g of attapulgite powder was still supplemented by granulated blast furnace slag powder. The remaining composition, dosage, mixing, tensioning, centrifugation, unloading, and curing conditions were the same as those in Comparative Example 1.

[0058] Comparative Example 3: Based on Comparative Example 1, at the point when the additives were added after the main wet mixing was completed, 18g of the supplementary additives were replaced with 18g of attapulgite powder of equal mass using granulated blast furnace slag powder, and the attapulgite powder was directly added to the main mixer; aluminum sulfate octahydrate was not added, and the missing 33.5g of aluminum sulfate octahydrate was still supplemented with granulated blast furnace slag powder. The remaining composition, dosage, mixing, tensioning, centrifugation, unloading, and curing conditions were the same as in Comparative Example 1.

[0059] Comparative Example 4: The final composition and dosage of each raw material were the same as in Example 1, but no thixotropic slag additive was formed outside the main mixer. First, 697.5g of lime-conditioned slag slurry, consisting of 400g granulated blast furnace slag powder, 22.5g calcium hydroxide, and 275g water, was prepared according to Comparative Example 1. After the main concrete was wet-mixed for 60 seconds, the lime-conditioned slag slurry, 18g attapulgite powder, and an aqueous solution consisting of 33.5g aluminum sulfate octahydrate and 101g water were added simultaneously. The components did not come into contact with each other before entering the main mixer, and mixing continued for 90 seconds after addition. The tensioning, centrifugation, plastic stage unloading, and curing regimes were all the same as in Example 1.

[0060] Comparative Example 5: The raw material composition, theoretical total mass of feed, lime conditioning process, addition process of aluminum sulfate octahydrate aqueous solution, additive dosage, and addition time of the slag thixotropic additive are all the same as in Example 1; the only difference is that 36g of attapulgite powder is added all at once before the aluminum sulfate octahydrate aqueous solution is added, and no second part of attapulgite powder is added afterwards. The concrete mixing, tensioning, centrifugation, unloading during the plastic stage, and curing regime are all the same as in Example 1.

[0061] Comparative Example 6: The final raw material composition, dosage, the ratio of attapulgite powder added in two stages, and the timing of additive addition were all the same as in Example 1; the only difference was the omission of calcium hydroxide pre-conditioning of granulated blast furnace slag powder. First, a slurry was formed using 550g water and 800g granulated blast furnace slag powder. Then, following the order in Example 1, two stages of attapulgite powder and a solution formed from 67g aluminum sulfate octahydrate and 202g water were added, theoretically yielding 1.655kg of slurry. 827.5g of this slurry was used for each batch of concrete, and 22.5g of calcium hydroxide was added simultaneously with the slurry after the main wet mixing was completed. The remaining mixing, tensioning, centrifugation, unloading during the plastic stage, and curing conditions were all the same as in Example 1.

[0062] Comparative Example 7: Using 850g of slag thixotropic additive with the same composition and formation process as in Example 1, but adding it simultaneously with 1.400kg of water containing a water-reducing agent at the start of the main wet mixing, followed by continuous wet mixing for 150s. In Example 1, the additive was added after 60s of main wet mixing and mixing continued for 90s, with a total wet mixing time of 150s for both. The remaining composition, tensioning, centrifugation, unloading during the plastic stage, and curing conditions were the same as in Example 1.

[0063] Comparative Example 8: The raw material composition, additive formation and feeding, temporary tension level, and centrifugation regime were all the same as in Example 1; the only difference was that after centrifugation, the material was not unloaded when the penetration resistance was 0.5 MPa, but instead, a tension of 48 kN was maintained. The temperature-time program for mold closing, heating rate, heat preservation, cooling, demolding, and subsequent curing from the end of centrifugation was the same as in Example 1; when the penetration resistance of the mortar screened from the same pan reached 3.5 MPa, the tension was reduced to 0 according to the same 120-second unloading process as in Example 1, and the temperature-time program was not recalculated or changed during or after unloading.

[0064] Comparative Example 9: The raw material composition, additive formation and feeding, material distribution, centrifugation and curing system are the same as in Example 1; the only difference is that the longitudinal reinforcing bars are not temporarily tensioned simultaneously, and the reinforcing cage is kept in position by the spiral bars, the support ring and the positioning parts at the end of the mold.

[0065] Test Results and Result Analysis Comparative Example 4 samples were prepared in parallel with the components added after the main wet mixing of Comparative Example 4, according to their proportions. Samples were taken after mixing for 90 seconds without adding cement or aggregate, and were used solely for material condition testing. No concrete rods were added. Test results are shown in Table 1.

[0066]

[0067] The centrifugal radial stratification index and 0.1 mm slip grip stress for each embodiment and comparative example are shown in Table 2.

[0068]

[0069] The changes in 1-day compressive strength, initial setting time, and 28-day length for each embodiment and comparative example are shown in Table 3.

[0070]

[0071] The results of residual stress and radial position of longitudinal reinforcing bars are shown in Table 4.

[0072]

[0073] As shown in Table 1, the additives in Comparative Example 5 and Comparative Example 4 had the same raw material composition and dosage. The difference was that Comparative Example 5 had an independent additive pre-formed before entering the main mixer. The absorbance of the aluminum reagent decreased from 0.428 in Comparative Example 4 to 0.126 in Comparative Example 5, and the absorbance of the barium sulfate turbidity decreased from 0.612 to 0.228. The increase in the mass of the solid phase after washing increased from 1.3% to 4.4%, indicating that the aluminum-containing components and sulfate-related components in the filtrate decreased during the pre-treatment process, and the mass of the solid phase retained after washing increased.

[0074] As shown in Table 1, under the same additive composition, dosage, and other formation conditions, Example 1, compared to Comparative Example 5, only changed the addition of attapulgite powder from a single, all-in-one addition to a two-stage addition. The static height retention rate increased from 84% to 91%, and the post-shear structure recovery rate increased from 68% to 82%. This indicates that the two-stage addition method—first adding the first portion of attapulgite powder, then adding the aluminum sulfate octadecylhydrate aqueous solution while continuing stirring, and finally adding the second portion of attapulgite powder—is beneficial for improving the static stability of the slurry additive and the post-shear structure recovery.

[0075] As shown in Tables 2 and 3, under the condition of no attapulgite powder and with the other components and process conditions being the same, Comparative Example 2, compared to Comparative Example 1, only had a portion of the granulated blast furnace slag powder replaced by an equal amount of aluminum sulfate octadecylhydrate. The centrifugal radial stratification index changed from 0.162 to 0.132, the 1-day compressive strength changed from 17.2 MPa to 20.9 MPa, the initial setting time changed from 222 min to 129 min, and the 0.1 mm slip bond stress changed from 7.8 MPa to 7.3 MPa. This indicates that under the condition of no attapulgite powder, replacing a portion of the granulated blast furnace slag powder with an equal amount of aluminum sulfate octadecylhydrate can reduce the centrifugal radial stratification index and increase the 1-day compressive strength, but shortens the initial setting time and reduces the 0.1 mm slip bond stress.

[0076] As shown in Tables 2 and 3, under the condition of no aluminum sulfate octadechydrate and with the other components and process conditions being the same, Comparative Example 3, compared to Comparative Example 1, only had a portion of the granulated blast furnace slag powder replaced by an equal mass of attapulgite powder. The centrifugal radial stratification index changed from 0.162 to 0.121, the 0.1 mm slip bond stress changed from 7.8 MPa to 7.0 MPa, and the 1-day compressive strength changed from 17.2 MPa to 16.5 MPa. This indicates that under the condition of no aluminum sulfate octadechydrate, replacing a portion of the granulated blast furnace slag powder with an equal mass of attapulgite powder can reduce the centrifugal radial stratification index, but the 0.1 mm slip bond stress and 1-day compressive strength decrease.

[0077] Table 2 shows that, under the conditions of the same amount of aluminum sulfate octahydrate, the same lime conditioning of the slag slurry, and the addition of each component after the main wet mixing, Comparative Example 4, compared to Comparative Example 2, only replaced 18g of granulated blast furnace slag powder with 18g of attapulgite powder by the same mass. The centrifugal radial stratification index changed from 0.132 to 0.088, and the 0.1mm slip bond stress changed from 7.3MPa to 7.7MPa. This indicates that in the direct feeding system containing aluminum sulfate octahydrate, the addition of attapulgite powder is beneficial in reducing the centrifugal radial stratification index and increasing the 0.1mm slip bond stress.

[0078] As shown in Tables 2 and 3, under the conditions of the same amount of attapulgite powder, the same lime conditioning of the slag slurry, and the addition of each component after the main wet mixing, Comparative Example 4, compared to Comparative Example 3, only replaced 33.5g of granulated blast furnace slag powder with 33.5g of aluminum sulfate octadechydrate. The centrifugal radial stratification index changed from 0.121 to 0.088, the 0.1mm slip bond stress changed from 7.0MPa to 7.7MPa, and the 1-day compressive strength changed from 16.5MPa to 20.5MPa. This indicates that in a direct feeding system containing attapulgite powder, the addition of aluminum sulfate octadechydrate is beneficial in reducing the centrifugal radial stratification index and increasing the 0.1mm slip bond stress and 1-day compressive strength.

[0079] Table 2 shows that, under the same composition, dosage, additive addition time, and other process conditions, Comparative Example 5, compared to Comparative Example 4, only had each component pre-formed as an independent additive before entering the main mixer. The centrifugal radial stratification index changed from 0.088 to 0.079, and the 0.1 mm slip bond stress changed from 7.7 MPa to 8.3 MPa. This indicates that pre-forming the slag thixotropic additive outside the main mixer and metering it in after the main wet mixing process is beneficial for balancing centrifugal radial uniformity and steel bond.

[0080] As shown in Tables 2 and 3, under the same additive composition, dosage, and other process conditions, Example 1, compared to Comparative Example 5, only changed the addition of attapulgite powder from a single, all-in-one addition to a two-stage addition. The centrifugal radial stratification index changed from 0.079 to 0.071, the 0.1 mm slip bond stress changed from 8.3 MPa to 8.9 MPa, and the initial setting time changed from 156 min to 164 min. This indicates that the two-stage addition method is beneficial for improving centrifugal radial uniformity and rebar bond; in this direct comparison, the initial setting time was extended from 156 min to 164 min.

[0081] As shown in Tables 2 and 3, under the same final composition, the same ratio of attapulgite powder added in both stages, and the same timing of additive addition, Example 1, compared to Comparative Example 6, only changed the addition of calcium hydroxide from the main wet mixing stage to pre-conditioning granulated blast furnace slag powder. The centrifugal radial stratification index changed from 0.086 to 0.071, the 0.1 mm slip bond stress changed from 8.0 MPa to 8.9 MPa, and the 1-day compressive strength changed from 19.4 MPa to 21.8 MPa. This indicates that, under the same final composition, using calcium hydroxide pre-conditioning granulated blast furnace slag powder is beneficial for reducing the centrifugal radial stratification index and increasing the 0.1 mm slip bond stress and 1-day compressive strength.

[0082] As shown in Tables 2 and 3, when using the same slag thixotropic additive and the same total wet mixing time, Example 1, compared to Comparative Example 7, only changed the addition of the additive from the start of wet mixing to after the main wet mixing was completed. The centrifugal radial stratification index changed from 0.084 to 0.071, the 0.1 mm slip bond stress changed from 7.9 MPa to 8.9 MPa, and the 1-day compressive strength changed from 21.5 MPa to 21.8 MPa. This indicates that adding the slag thixotropic additive after the main wet mixing is beneficial for reducing the centrifugal radial stratification index and increasing the 0.1 mm slip bond stress; in this direct comparison, the 1-day compressive strength changed from 21.5 MPa to 21.8 MPa.

[0083] As shown in Tables 2 and 3, the centrifugal radial stratification indices of Examples 2, 1, and 3 are 0.089, 0.071, and 0.064, respectively; the 0.1 mm slip bond stresses are 9.2 MPa, 8.9 MPa, and 8.2 MPa, respectively; the 1-day compressive strengths are 18.9 MPa, 21.8 MPa, and 23.5 MPa, respectively; the initial setting times are 195 min, 164 min, and 128 min, respectively; and the 28-day length changes are -168 με, -65 με, and +46 με, respectively. All three examples, under their respective listed compositions and process conditions, formed complete annular rod segments.

[0084] As shown in Table 4, with the same composition, temporary tension level, centrifugation regime, and temperature-time program from the end of centrifugation, Example 1, compared to Comparative Example 8, only advanced the unloading point from the penetration resistance stage of 3.5 MPa to the plastic stage where the penetration resistance was 0.5 MPa and no heating was applied. The 28-day converted average residual compressive stress changed from 0.740 MPa to 0.081 MPa, and the residual stress transfer rate changed from 32.80% to 3.59%. This indicates that completely removing the external tension before heating and curing can reduce the prestress transmitted to the rod through the bond formed by the rebar shrinkage. Both residual stress indices of Example 1 are within the non-prestressed boundary specified in this specification.

[0085] As shown in Tables 2 and 4, under the same material composition, fabric, centrifugation, and curing conditions, Example 1, compared to Comparative Example 9, only added temporary synchronous tensioning during molding and complete unloading during the plastic stage. The maximum radial position deviation of the longitudinal reinforcing bars changed from 2.4 mm to 0.6 mm, the 0.1 mm slip-bond stress changed from 7.9 MPa to 8.9 MPa, the 28-day converted residual average compressive stress was 0.081 MPa, and the residual stress transfer rate was 3.59%. This indicates that temporary synchronous tensioning is beneficial for maintaining the straightness and circumferential stability of the longitudinal reinforcing bars; the residual stress results of Example 1 are within the non-prestressed boundary specified in this specification.

[0086] Figure 2 Complete load-slip curves for Example 1, Comparative Example 4, Comparative Example 5, and Comparative Example 9 are presented. At a slip of 0.1 mm, the grip stress in Example 1 is higher than that in Comparative Examples 4, 5, and 9; all curves decrease continuously after reaching their peak values, and no sudden drop occurs in the initial loading stage.

[0087] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A tensioned non-prestressed concrete pole, comprising a hollow annular concrete pole body and a reinforcing cage embedded in the concrete pole body, the reinforcing cage comprising longitudinal reinforcing bars spaced apart along the circumference of the concrete pole body, helical bars wound around the outside of the longitudinal reinforcing bars, and a support ring connecting the longitudinal reinforcing bars, characterized in that, The concrete pole is formed from a concrete mixture containing ordinary silicate cement, granulated blast furnace slag powder, medium sand, crushed stone, polycarboxylate superplasticizer, water, and slag thixotropic additive. The total mass of the ordinary silicate cement and all the granulated blast furnace slag powder is 100 parts by mass, with the ordinary silicate cement being 60-62 parts by mass and the granulated blast furnace slag powder being the balance, totaling 100 parts by mass. The medium sand is 165-168 parts by mass, the crushed stone is 252-255 parts by mass, the polycarboxylate superplasticizer is 0.9-1.0 parts by mass, the total water is 32-34 parts by mass, and the wet dosage of the slag thixotropic additive is 13-19 parts by mass. The granulated blast furnace slag powder in the slag thixotropic additive is 100 parts by weight. The slag thixotropic additive contains 89.5-99.5 parts by weight of water, 4-7 parts by weight of calcium hydroxide, 6-10 parts by weight of aluminum sulfate octadecylhydrate, and 3-6 parts by weight of attapulgite powder. The water in the slag thixotropic additive is added liquid water during the preparation of the additive, and the total water is the sum of the added liquid water directly added to the main concrete and the water in the slag thixotropic additive. The slag thixotropic additive is a slurry additive that is independently prepared and metered in after the main wet mixing of the concrete mixture is completed. The slag thixotropic additive is formed by pre-dispersing granulated blast furnace slag powder and calcium hydroxide in an aqueous phase to form a lime-conditioned slag slurry, adding a first part of attapulgite powder to the lime-conditioned slag slurry, then adding an aqueous solution of aluminum sulfate octahydrate, and then adding a second part of attapulgite powder. The granulated blast furnace slag powder and water contained in the slag thixotropic additive are respectively included in the mass fraction of all granulated blast furnace slag powder and total water. The concrete bar is formed by placing and centrifuging the longitudinal reinforcing bars under temporary tension, and then completely removing the external tension of the longitudinal reinforcing bars after centrifugation and before heating and curing while the concrete is still in the plastic stage. The longitudinal reinforcing bars in the finished product are non-prestressed reinforcing bars.

2. The tensioned non-prestressed concrete pole according to claim 1, characterized in that, With the total mass of the ordinary silicate cement and all granulated blast furnace slag powder as 100 parts by mass, the granulated blast furnace slag powder contained in the slag thixotropic additive accounts for 15.7% to 22.4% of the total granulated blast furnace slag powder; the ratio of the total water to the total mass of the ordinary silicate cement, all granulated blast furnace slag powder, calcium hydroxide, aluminum sulfate octadecylhydrate and attapulgite powder is 0.316 to 0.

332.

3. The tensioned non-prestressed concrete pole according to claim 1, characterized in that, The first part of the attapulgite powder accounts for 40% to 60% of the total mass of the attapulgite powder, and the second part of the attapulgite powder is the remainder.

4. The tensioned non-prestressed concrete pole according to claim 1, characterized in that, The longitudinal reinforcing bars are 12 HRB400 hot-rolled ribbed steel bars with a nominal diameter of 8mm, and the spiral bars and support rings are HPB300 plain round steel bars. The 12 longitudinal reinforcing bars are evenly distributed along the circumference of the concrete pole.

5. A method for preparing a tensioned non-prestressed concrete pole according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Granulated blast furnace slag powder and calcium hydroxide are added to water for pre-dispersion to form lime-conditioned slag slurry; (2) Add the first part of attapulgite powder to the lime-conditioned slag slurry, stir, add aluminum sulfate octahydrate aqueous solution, continue stirring, and then add the second part of attapulgite powder to obtain an independent slag thixotropic additive. (3) Dry mix crushed stone, medium sand, ordinary silicate cement and granulated blast furnace slag powder directly into the main mixer, add water containing polycarboxylate superplasticizer for main wet mixing, and then add the slag thixotropic additive after the main wet mixing is completed and continue mixing to obtain centrifugal concrete. (4) Fabricate a steel cage containing longitudinal reinforcing bars, spiral bars and support rings, and temporarily tension the longitudinal reinforcing bars simultaneously, maintaining the temporary tension state to complete the placement, formwork closing and graded centrifugation of the centrifuged concrete; (5) After centrifugation, the external tension is completely removed to 0 while the concrete is still in the plastic stage and is not heated, and the external tension connection is removed; then low temperature curing, demolding and subsequent curing are carried out.

6. The preparation method according to claim 5, characterized in that, When forming the lime-conditioned slag slurry, the water temperature is controlled at 25°C. Granulated blast furnace slag powder and calcium hydroxide are added while stirring at 400 r / min, and then the stirring speed is increased to 500-700 r / min for 8-12 min. After adding the first part of attapulgite powder, the mixture is stirred for 2 min. Within 3-5 min, an aqueous solution of aluminum sulfate octadecylhydrate is added and stirring is continued for 5-8 min. After adding the second part of attapulgite powder, the mixture is stirred for 8-12 min. The resulting slag thixotropic additive is self-made and can be stored in a sealed container. It is then added to the centrifugal concrete within 40 min.

7. The preparation method according to claim 5, characterized in that, The crushed stone, medium sand, ordinary silicate cement, and granulated blast furnace slag powder directly added to the main mixer are dry-mixed for 30 seconds, then wet-mixed with water containing polycarboxylate-based high-efficiency water-reducing agent for 60 seconds, and then mixed for 60-120 seconds after adding the slag thixotropic additive.

8. The preparation method according to claim 5, characterized in that, Temporary tension control stress of 60-100 MPa is applied to the longitudinal reinforcing bars, and the load is sequentially applied to 20%, 60% and 100% of the corresponding total tension force. The first two stages are held for 30 seconds each, and the last stage is held for 60 seconds. The graded centrifugation includes running at 150 r / min for 2 minutes, at 400 r / min for 3 minutes and at 800 r / min for 6 minutes, with a uniform speed increase of 30 seconds between adjacent stages.

9. The preparation method according to claim 5, characterized in that, After centrifugation stops, keep the mold closed and do not heat it. When the penetration resistance of the mortar screened out of the same disc is 0.3 to 0.8 MPa, start unloading. First, reduce the external tension force to 50% of the total temporary tension force within 30 seconds, and then reduce the external tension force to 0 uniformly within 60 to 120 seconds. After unloading is completed, remove the external tension connection, and no further axial tension force will be applied to the longitudinal reinforcing steel in subsequent steps.

10. The preparation method according to claim 5, characterized in that, After completely removing the external tension, the mold was closed and left to stand for 10 minutes. The temperature was then increased to 40℃ at a rate of 10℃ / h and kept at that temperature for 6 hours. After that, the heating was stopped and the mold was allowed to cool down in the curing chamber. After the mold was closed for 12 hours and the compressive strength of the concrete specimen under the same conditions reached 15MPa, the specimen was demolded. After demolding, the specimen was cured at 20℃ and 95% relative humidity for 28 days.